Pengurusan Pembangunan Daerah Negeri Kedah Darul Aman : Satu Kajian Ke Atas Agenda Pembangunan Dalam Minit Mesyuarat Jawatankuasa Pembangunan Daerah Negeri Kedah - Mohammad Hasnan, Hassan (1997)
This study was undertaken to observe the rural community development management in the State of Kedah Darul Aman by observing the strategy of development management. The role and function of the JKKK (Village Security and Development Committee) is the main focus in this study. The main task of the JKKK is to coordinate development, social and security activities. It is also the major channel for the village community to express needs in the national development. The ‘library research’ approach is used to examine the development management and the roles and function of the JKKK. The ‘content analysis’ method is used to examine the total of 52 minutes of selected District’s Development Committee meeting. The results showed that the pattern of the development in Kedah is balanced towards the State development strategy. The aspects of the development mainly focused on infrastructure, economy and social development. The development in the State showed that there were an understanding and balancing within the guidelines of the MENJARO and POLEMAS that was introduced by the State leadership.